(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this study was to analyze the evolution of Brazilian exports of wooden doors from 2005 to 2015 regarding the degree of inequality. In order to determine the inequality, the Gini Index was used. To that end, monetary values of exports were collected in the UNCONTRADE database and deflated, using empirically the base year 2005. The results showed that the Brazilian exports of wooden doors were characterized by very strong to absolute inequality. In addition, the absolute value of exports for the period analyzed increased from US 227.3 million in 2005 to US 154.3 million in 2015. In this way, this analysis indicates that Brazil should expand its exports, it is of fundamental importance the interaction between the organizations and the government, aiming at elaborating and perfecting strategies that allow the competitiveness of the Brazilian product in relation to the other exporters.